IMPACT OF COMMON CHRONIC DISEASES ON SEMEN QUALITY: A NARRATIVE REVIEW - Wiktor Śliwiński; Dominika Matecka; Jakub Mazur; Daniel Chołuj; Weronika Pura; Karolina Zarówna; Mateusz Kosowski; Jakub Marciniak (International Journal of Innovative Technologies in Social Science, 2026)
Background. Chronic diseases, including obesity, type 2 diabetes, cardiovascular diseases, and autoimmune conditions, represent a significant threat to male fertility. These conditions disrupt testicular homeostasis through interconnected pathophysiological mechanisms, leading to the deterioration of semen parameters and sperm genomic integrity. Aim. This narrative review aims to analyze the impact of common chronic diseases on semen quality and to discuss the integrated molecular and systemic mechanisms underlying male infertility in these clinical conditions. Material and methods. A narrative review of current scientific literature was conducted, focusing on clinical and experimental studies regarding the effects of metabolic, cardiovascular, autoimmune, renal, and hepatic disorders on male reproductive functions. Key pathomechanisms, including oxidative stress, inflammation, and hormonal dysregulation, were analyzed. Results. Five primary pathways leading to testicular dysfunction were identified: (1) oxidative stress causing lipid peroxidation and decreased sperm motility; (2) chronic inflammation disrupting the blood-testis barrier; (3) HPG axis dysregulation leading to hypogonadism; (4) endothelial dysfunction impairing testicular microcirculation and thermoregulation; and (5) sperm DNA damage. It was shown that patients with diabetes, hypertension, and inflammatory joint diseases exhibit significantly lower sperm concentration, volume, and motility compared to control groups. Conclusions. Chronic diseases exert a multidirectional, negative impact on semen quality, and the degree of fertility impairment often correlates with disease activity and stage. Management of metabolic and cardiovascular health, along with inflammatory control, is crucial for preserving male reproductive potential.